A WBEM based solution for a 4G network integrated management - Goncalves, Pedro
Next generation networks will put a new set of challenges related to operation and management, due to the increased complexity arising by the seamless integration of different kinds of technologies, services and terminals, and with the expected offered bandwidth. In this paper we present a Policy-based management system that is being developed inside the Daidalos IST project for such environments. This system uses Policy Based Management concepts associated with Web-Based Enterprise Management to control QoS aspects in this complex network.